Design of Citizen Fund Management Applications in Village Level Communities: Case Study: Financial Manager for Pandanaran Village Residents, Banjarnegara - Choirul Arif; Arifudin Hamzah; Himmatur Reza (Universitas Amikom Purwokerto, 2023)
Information technology, in general, can provide convenience for users in projecting data processing systems, in recording and recapping annual calculations as a distribution of the results of village-level fund management (